Investigation of suspected Newcastle disease (ND) outbreaks in Egypt uncovers a high virus velogenic ND virus burden in small-scale holdings and the presence of multiple pathogens. Issue 5 (3rd September 2019) - Moharam, Ibrahim; Razik, Alaa Abd el; Sultan, Hesham; Ghezlan, Mohammed; Meseko, Clement; Franzke, Kati; Harder, Timm; Beer, Martin; Grund, Christian
ABSTRACT: Highly contagious Newcastle disease (ND) is associated with devastating outbreaks with highly variable clinical signs among gallinaceous birds. In this study we aimed to verify clinical ND suspicions in poultry holdings in Egypt suffering from respiratory distress and elevated mortality, comparing two groups of ND-vaccinated poultry holdings in three governorates. Besides testing for Newcastle disease virus (NDV), samples were screened for infectious bronchitis virus (IBV) and avian influenza virus (AIV) by RT-qPCR as well as by non-directed cell-culture approach on LMH-cells. Virulent NDV was confirmed only in group A ( n = 16) comprising small-scale holdings. Phylogenetic analysis of the fusion protein gene of 11 NDV-positive samples obtained from this group assigned all viruses to genotype 2.VIIb and point to four different virus populations that were circulating at the same time in one governorate, indicating independent epidemiological events. In group B, comprising large commercial broiler farms ( n = 10), virulent NDV was not present, although in six farms NDV vaccine-type virus (genotype 2.II) was detected. Besides, in both groups, co-infections by IBV ( n = 10), AIV H9 ( n = 3) and/or avian reovirus (ARV) ( n = 5) and avian astrovirus (AastVs) ( n = 1) could be identified. Taken together, the study confirmed clinical ND suspicion in small scale holdings, pointing to inefficient vaccination practices in this group A. However, it also highlighted that, even in an endemic situation like ND in Egypt, in cases of suspected ND vaccine failure, clinical ND suspicion has to be verified by pathotype-specific diagnostic tests. RESEARCH HIGHLIGHTS Velogenic NDV circulates in small-scale poultry holdings in Egypt. Viral transmission occurred among neighbouring farms and over long distances. Co-infections with multiple pathogens were identified. Pathotype specific diagnostic tests are essential to verify ND suspicions.